LiteITD a MATLAB Graphical User Interface (GUI) program for topology design of continuum structures. (October 2016) - Victoria, Mariano; Querin, Osvaldo M.; Díaz, Concepción; Martí, Pascual
Highlights: liteITD (lite version of Isolines Topology Design) software package. Topology optimization of 2D continuum structures using von Mises stress isolines. The liteITD program was completely designed using MATLAB GUI environment. The liteITD can be downloaded from http://www.upct.es/goe/software/liteITD.php . Abstract: Over the past few decades, topology optimization has emerged as a powerful and useful tool for the design of structures, also exploiting the ever growing computational speed and power. The design process has also been affected by computers which changed the concept of form into the concept of formation and the emergence of digital design. Topology optimization can modify existing designs, incorporate explicit features into a design and generate completely new designs. This paper will show how topology optimization can be used as a digital tool. The liteITD (lite version of Isolines Topology Design) software package will be described with the purpose of providing a tool for topology design. The liteITD program solves the topology optimization of two-dimensional continuum structures using von Mises stress isolines under single or multiple loading conditions, with different material properties in tension and compression, and multiple materials. The liteITD program is fully implemented in the MATrix LABoratory (MATLAB) software environment of MathWorks under Windows operating system. GUIDE (Graphical User Interface Development Environment) was used to create a friendly Graphical User Interface (GUI). The usage of this application is directed to students mainly (educational purposes), although also to designers and engineers with experience. The liteITD program can be downloaded and used for free from the website: http://www.upct.es/goe/software/liteITD.php .